Factors affecting health risk behaviors of tangerine farmers in Si Satchanalai District Sukhothai Province - Kanmud, Siriyakorn; Hinhumpatch, Pantip; Juksu, Kanokthip (Disease Control Journal, 2023)
The cross-sectional descriptive research aimed to study the level of health risk behaviors and to study factors affecting the health risk behaviors among tangerine farmers in Si Satchanalai District, Sukhothai Province. The sample consisted of representatives of 230 registered tangerine farming households, selected using a simple random sampling technique. The data collection was collected using questionnaires and analyzed using the frequency distribution, percentage, Eta, Pearson correlation, and stepwise multiple regression analysis. The results revealed that the majority of tangerine farming households had high levels of knowledge, perception, and behaviors towards health risk behaviors related to work at 88.70%, 94.30%, and 91.30%, respectively. The significant predictors of health risk behaviors related to work included income (Beta=0.195), drinking alcohol (Beta = 0.215), enabling factors (Beta=0.209), smoking (Beta=0.133) and reinforcing factors (Beta=0.134), which able to predict approximately 16.90% at p-value less than 0.05). Therefore, related agencies should give priority to health and safety in work as well as raise awareness and change health risk behaviors among tangerine farmers.